Nineteenth-century Shakespeares: nationalism and moralism - Hollingsworth, Mark (2007)
This thesis shows that 'Shakespeare' (both the works and the man) was at the forefront of literary activity in the nineteenth century. By focusing on concerns about the identity of the British nation and its people it shows that Shakespeare was a constant presence in the debates of the day and that a number of agendas were pursued through what were ostensibly writings about Shakespeare's plays and the biography of their author.